Influence of mechanical-thermal treatment on the microstructure and current-carrying capacity of Nb-Ti-superconductor - Storozhilov, G.E.; Andrievskaya, N.F.; Tikhonovsky, M.A. (Вопросы атомной науки и техники, 2020)
A correlation between the modes of mechanical-thermal treatment, main microstructure parameters and the critical current density Jc in the superconducting alloy Nb-49 wt.% Ti was established. The studies were carried out on the alloy that was preliminary deformed by the “upsetting-extrusion” severe plastic deformation (SPD) method and subsequently drawn with multiple intermediate heat treatments (HT) at 390 °C for 400 and 2000 h. After completion of the heat treatments, the superconductor was finally drawn with the degree of deformation efin. It was shown that the volume fraction of a-Ti phase precipitates increases with the increasing in number of heat treatments up to ≈ 24 and 27% for a total heat treatment duration of 400 and 2000 h, respectively, and reaches maximum values at HT quantity of 4-5 and 7. The highest critical current density level in a magnetic field 5 T, Jc ≈ 3.8*105 A/cm2, was obtained for a total heat treatments duration of 2000 h, 7 number of HT and final true strain ≈ 5.05. The dependence of the pinning volume force Fp on the reduced magnetic field b in such superconductor is described by a function in form Fp ~ b(1-b)2, a characteristic of superconducting materials with strong vortex magnetic lattice on the precipitates. Встановлено взаємозв'язок між режимами механіко-термічної обробки, основними параметрами мікроструктури і густиною критичного струму Jc у надпровідному сплаві Nb-49 мас.% Ti. Дослідження проведені на сплаві, який піддавався попередній інтенсивній пластичній деформації (ІПД) методом «осаджування-видавлювання» і подальшому волочінню з багаторазовими проміжними термообробками (ТО) при температурі 3900С протягом 400 і 2000 год. Показано, що об'ємна частка виділень a-Ti-фази збільшується зі зростанням кількості термічних обробок аж до ≈ 24 і 27% при сумарній тривалості ТО 400 і 2000 год відповідно, досягаючи максимальних значень при кількості ТО 4-5 і 7. Найбільший рівень густини критичного струму в магнітному полі 5 Тл Jc ≈ 3,8*105 А/см2 отримано при загальній тривалості ТО 2000 год, їх кількості 7 і заключній істинній деформації ≈ 5,05. Залежність об'ємної сили піннінга Fp від наведеного магнітного поля b у такому надпровіднику описується функцією виду Fp ~ b(1-b)2, яка характерна для надпровідних матеріалів з сильним піннінгом вихрової магнітної решітки на виділеннях. Установлена взаимосвязь между режимами механико-термической обработки, основными параметрами микроструктуры и плотностью критического тока Jc в сверхпроводящем сплаве Nb-49 мас.% Ti. Исследования проведены на сплаве, который подвергался предварительной интенсивной пластической деформации (ИПД) методом «осадки-выдавливания» и последующему волочению с многократными промежуточными термообработками (ТО) при температуре 390 0С в течение 400 и 2000 ч. После завершения ТО сверхпроводник проходил заключительное волочение со степенью деформации еfin. Показано, что объемная доля выделений a-Ti-фазы увеличивается с ростом количества термических обработок вплоть до ≈ 24 и 27% при суммарной длительности ТО 400 и 2000 ч соответственно, достигая максимальных значений при количестве ТО 4-5 и 7. Наибольший уровень плотности критического тока в магнитном поле 5 Тл Jc ≈ 3,8*105 А/см2 получен при общей длительности ТО 2000 ч, их количестве 7 и заключительной истинной деформации ≈ 5,05. Зависимость объемной силы пиннинга Fp от приведенного магнитного поля b в таком сверхпроводнике описывается функцией вида Fp ~ b(1-b)2, характерной для сверхпроводящих материалов с сильным пиннингом вихревой магнитной решетки на выделениях.